Will HIPC matter? The debt game and donor behaviour in Africa - Nancy Birdsall; Stijn Claessens; Ishac Diwan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In this paper we focus on the question: will the HIPC debt reduction programme help in the transformation of the development assistance business and change the rules of the `debt game' in Africa? We concentrate on the donor and official creditor side, by exploring how the growing debt of African countries, over the last two decades, has affected the provision of new resources by the donor community. Our results indicate that if debt levels are reduced sufficiently in high debt countries, donors can shift from the current pattern of non-selectivity and defensive lending to a low debt regime, a regime that has in the past allowed selectivity in lending in relation to levels of poverty and quality of policy.
Keywords: O11; O19; F34; F35; 330; debt relief; foreign aid; low-income countries; international organizations; Schuldenerlass; Entwicklungshilfe; Entwicklungsprojekt; Afrika